2023
DOI: 10.1021/acs.orglett.3c00262
|View full text |Cite
|
Sign up to set email alerts
|

Cu-Catalyzed Asymmetric Alkenylation of Enone Diesters with Trialkenylboroxines

Abstract: The Cu-catalyzed asymmetric conjugate addition of trialkenylboroxines to enone diesters is reported. This operationally simple and scalable reaction proceeded at room temperature, and a wide range of enone diesters and boroxines were tolerated under the applied reaction conditions. The practical utility of this approach was demonstrated via the formal synthesis of (+)-methylenolactocin. Mechanistic studies revealed that two different catalytic species work synergistically in the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…As part of continuous efforts in asymmetric allylation reactions by N , N ′-dioxide/metal complexes 8,9 and motivated by our previous research on the construction of α-methylene-γ-butyrolactones via the asymmetric allylboration/lactonization reaction, 10 we envisaged that the stereoselective allylation of enone diesters 11 could produce α,β-unsaturated-γ-hydroxy ester intermediates, which may undergo subsequent lactonization to afford the corresponding chiral butenolides (Scheme 1c). Herein, we wish to report our endeavor along this line.…”
mentioning
confidence: 99%
“…As part of continuous efforts in asymmetric allylation reactions by N , N ′-dioxide/metal complexes 8,9 and motivated by our previous research on the construction of α-methylene-γ-butyrolactones via the asymmetric allylboration/lactonization reaction, 10 we envisaged that the stereoselective allylation of enone diesters 11 could produce α,β-unsaturated-γ-hydroxy ester intermediates, which may undergo subsequent lactonization to afford the corresponding chiral butenolides (Scheme 1c). Herein, we wish to report our endeavor along this line.…”
mentioning
confidence: 99%
“…Enone diesters are valuable building blocks, and various nucleophiles are known to undergo regio- and enantioselective conjugate additions (Scheme b). , We have previously reported the Cu-catalyzed asymmetric alkenylation of enone diesters with trialkenylboroxines as pronucleophiles (Scheme c) . Mechanistic studies suggested that two different Cu species work synergistically in the reaction.…”
mentioning
confidence: 99%
“…The reaction was also applicable to a heteroarylboronic acid, 3-thienylboronic acid ( 3p ). The alkenylation using styrylboronic acid was superior to the previously reported reaction using tristyrylboroxine in terms of the availability of the starting material and enantioselectivity ( 3q ) . The practical utility of this process was demonstrated by the preparation of 1.47 g of 3a in excellent enantioselectivity (Scheme ).…”
mentioning
confidence: 99%
See 1 more Smart Citation